Traditional Classroom Management to Virtual Classroom Management: A Study on Physical Education Teachers’ Competencies - Mustafa Enes Işıkgöz (SAGE Open)
This study investigated physical education teachers’ competencies in virtual classroom management. The study was designed as a cross-sectional study using quantitative research methods and included 726 physical education teachers working in different secondary and high schools in Turkey. The study data were collected using the “Teachers’ Virtual Classroom Management Competence Scale.” The research found that physical education teachers were still deciding about their competence in managing relationships with students in the virtual classroom. Still, they were competent in the dimensions of virtual classroom activities and virtual classroom management. Further research analyzed the effects of some sociodemographic variables on teachers’ competencies in transitioning from traditional classroom management to virtual classroom management. The analysis showed that gender and work experience had a medium effect, virtual classrooms had a significant impact, and school level had a weak effect on teachers’ virtual classroom competencies. The educational level variable did not significantly impact teachers’ online classroom management competencies. In conclusion, in modern classrooms with a shift from traditional classrooms to online classrooms, physical education teachers are expected to be more effective in their relationships with students in online classrooms.